Similar immune responses to alpha1‐oleate and Bacillus Calmette–Guérin treatment in patients with bladder cancer - Shahram Ahmadi; Ines Ambite; Antonín Brisuda; Jaromír Háček; Farhan Haq; Samudra Sabari; Kamala Vanarsa; Chandra Mohan; Marek Babjuk; Catharina Svanborg (Cancer Medicine, 2024)
Abstract Background The molecular content of urine is defined by filtration in the kidneys and by local release from tissues lining the urinary tract. Pathological processes and different therapies change the molecular composition of urine and a variety of markers have been analyzed in patients with bladder cancer. The response to BCG immunotherapy and chemotherapy has been extensively studied and elevated urine concentrations of IL‐1RA, IFN‐α, IFN‐γ TNF‐α, and IL‐17 have been associated with improved outcome. Methods In this study, the host response to intravesical alpha 1‐oleate treatment was characterized in patients with non‐muscle invasive bladder cancer by proteomic and transcriptomic analysis. Results Proteomic profiling detected a significant increase in multiple cytokines in the treatment group compared to placebo. The innate immune response was strongly activated, including IL‐1RA and pro‐inflammatory cytokines in the IL‐1 family (IL‐1α, IL‐1β, IL‐33), chemokines (MIP‐1α, IL‐8), and interferons (IFN‐α2, IFN‐γ). Adaptive immune mediators included IL‐12, Granzyme B, CD40, PD‐L1, and IL‐17D, suggesting broad effects of alpha 1‐oleate treatment on the tumor tissues. Conclusions The cytokine response profile in alpha 1‐oleate treated patients was similar to that reported in BCG treated patients, suggesting a significant overlap. A reduction in protein levels at the end of treatment coincided with inhibition of cancer‐related gene expression in tissue biopsies, consistent with a positive treatment effect. Thus, in addition to killing tumor cells and inducing cell detachment, alpha 1‐oleate is shown to activate a broad immune response with a protective potential.